Acute‐on‐chronic liver failure in children with biliary atresia awaiting liver transplantation. (30th December 2018) - D'Souza, Rashmi; Grammatikopoulos, Tassos; Pradhan, Akhilesh; Sutton, Harry; Douiri, Abdel; Davenport, Mark; Verma, Anita; Dhawan, Anil
Abstract: Objectives: Acute‐on‐chronic liver failure (ACLF) is an acute decompensation of cirrhosis complicated by other organ failure and is associated with increased mortality and morbidity. ACLF has not been studied in children with biliary atresia (BA), which is the commonest indication for pediatric liver transplantation (LT) worldwide. This study aims to evaluate ACLF and outcomes in children with BA while awaiting deceased donor LT. Methods: This was a subanalysis of the dataset from a prospective cohort study of patients aged 0‐18 years who underwent portoenterostomy for BA and were listed for LT at King's College Hospital, London, between 1999 and 2003. Outcomes included the development of ACLF, mortality, and complications. Results: Ninety‐nine (41 male) children were included, and follow‐up was 10 [6.0‐15.0] years. A total of 20/99 children developed ACLF. ACLF was associated with increased mortality while awaiting LT (20% vs 4%; P = 0.03). There were no associations between biochemical parameters at listing and death. Increased bilirubin levels 3 months post‐portoenterostomy was predictive of development of ACLF (AUROC = 0.72, P < 0.01). Age at LT and time on the waiting list in the ACLF subgroup were both lower compared to the non‐ACLF group ( P > 0.05). Sepsis and gastrointestinal bleeding were the commonest precipitants of ACLF. Complications included ascites, hepatic encephalopathy, and hepatorenal syndrome; the ACLF subgroup required multisystem support and longer intensive care unit stay. Conclusions: ACLF in children with BA awaiting deceased donor LT carries increased mortality and morbidity. This warrants stratification of patients for earlier wait‐listing and prioritization for LT.